Q. 54.1( 135 Votes )

# Find the value of

Answer :

Formula: = a(m-n)

am × an = a(m+n)

an = am, then n = m

By using above formula in question:

5m ÷ 5-3 = 55 ⇒ 5m - (-3) = 55

⇒ 5m+3 = 55

⇒ m + 3 = 5

⇒ m = 2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

If abc is a threeNCERT - Mathematics Exemplar

Let abc be a threNCERT - Mathematics Exemplar

The sum of all nuNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Let abc be a threNCERT - Mathematics Exemplar